Synthesis of Barium Titanate (BaTiO3) ceramics by Solid State Reaction - PHAKVISETH, Pem; SOMBOUM, Saokeo; PHIMMAVONG, Kongsy; LAMPHAYPHANH, Kittiphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This work focuses on the production of barium titanate powder using a solid-state reaction method. It will focus on experimenting with temperature in the production of barium titanate powder to make the powder into a dielectric material and analyze the electrical properties to transform it into an electronic device using X-ray diffraction technique called X-Ray Diffraction (XRD) in the preliminary analysis of identifying the phase and structure that occurs inside the powder as the desired outcome, the synthesis of barium titanate determined the molar ratio (1:1) by weight. The raw materials used in this experiment are barium carbonate (BaCO3) in an amount of 0.03 mole and titanium dioxide (TiO2) in the relation of 0.03 mole, and the raw materials are calcinated at 5 temperatures: 700°C, 800°C, 900°C, 1000°C, and 1100°C, with a temperature increase rate of 5°C per minute. The experiment found that calcinating at 700°C resulted in 81% BaCO3 and 19% TiO2, which cannot be combined as a barium titanate material. Being calcinated at 800°C to 900°C is going to show that there is a peak pattern of barium titanate, but it is still not completed. Calcinating at a temperature of 1000°C to 1100°C will be able to synthesize completely formed barium titanate according to the comparison of the results of the synthesis from (JCPDS XRD Database BaTiO3), which can synthesize barium titanate that meets the purpose, and we can bring this material to the next development in the process of forming or in the manufacturing process as a dielectric material, which is an important component in the capacitor.